A novel web-based calculator to predict 30-day all-cause in-hospital mortality for 7,202 elderly patients with heart failure in ICUs: a multicenter retrospective cohort study in the United States - Wang, Zhongjian; Huang, Jian; Zhang, Yang; Liu, Xiaozhu; Shu, Tingting; Duan, Minjie; Wang, Haolin; Yin, Chengliang; Cao, Junyi (Frontiers in Medicine, 2023)
Background and Aims: Heart failure (HF) is a significant cause of in-hospital mortality, especially for the elderly admitted to the intensive care units (ICUs). This study aimed to develop a web-based calculator to predict 30-day in-hospital mortality for the elderly patients with HF in ICU and found relationship between risk factors and predicted probability of death. Methods and Results: Data (N = 4450) from the MIMIC-III/IV database were used for training and internally testing model. Data (N = 2752) from the eICU-CRD database were used for external validation. The brier score and area under curve (AUC) were employed for assessment of proposed nomogram. Restrictive cubic splines (RCS) found the cutoff values of variables. The smooth curve showed the relationship between the variables and the predicted probability of death. A total of 7202 elderly patients with HF were enrolled, in which 1212 patients died.Multivariate logistic regression analysis showed that 30-day mortality of HF patients in ICU were significantly associated with heart rate (HR), 24 hour urine output (24H UOP), calcium, blood urea nitrogen (BUN), NT-proBNP, SpO2, systolic blood pressure (SBP) and temperature (P < 0.01). The AUC and Brier Score of the nomogram were 0.71 (0.67, 0.75) and 0.12 (0.11, 0.15) in the test set, and 0.73 (0.70, 0.75) and 0.13 (0.12, 0.15), and 0.65 (0.62,0.68) and 0.13 (0.12, 0.13) in the external validation set, respectively. RCS plot showed the cutoff value of factors were HR with 96 bmp, 24 h UOP with 1.2 L, calcium with 8.7 mg/dL, BUN with 30 mg/dL, NT-pro-BNP with 5121 pg/mL, SpO2 with 93%, SBP with 137 mmHg and 4 temperature with 36.4℃.: Decreased temperature, decreased SpO2, decreased 24h UOP, increased NT-proBNP, increased serum BUN, increased or decreased SBP, fast HR, and increased or decreased serum calcium increase the predicted probability of death. The web-based nomogram developed in this study showed good performance in predicting the 30-day in-hospital mortality for elderly HF patients in the ICU.